The post-discharge coping difficulty of puerperal women in a middle and low-income tourist city during the COVID-19 pandemic - Yan Liu; Lan-lan Peng; Yi-yuan Zhang; Mei-yin Tang; Mei-qiong Tang; Yun-yun Xu; Zong-ying Ma; Yi Tang; Lingling Gao (BMC, 2023)
Abstract Background Since the coronavirus disease 2019 (COVID-19) pandemic outbreak, the incidence of mental health problems in perinatal women has been high, and particularly prominent in China which was the first country affected by COVID-19. This paper aims to investigate the current situation and the related factors of maternal coping difficulties after discharge during COVID-19. Methods General information questionnaires (the Perinatal Maternal Health Literacy Scale, Postpartum Social Support Scale and Post-Discharge Coping Difficulty Scale-New Mother Form) were used to investigate 226 puerperal women in the third week of puerperium. The influencing factors were analyzed by single factor analysis, correlation and multiple linear regression. Results The total score of coping difficulties after discharge was 48.92 ± 12.05. At the third week after delivery, the scores of health literacy and social support were 21.34 ± 5.18 and 47.96 ± 12.71. There were negative correlations among health literacy, social support and coping difficulties after discharge (r = -0.34, r = -0.38, P < 0.001). Primipara, family income, health literacy and social support were the main factors influencing maternal coping difficulties after discharge. Conclusion During the COVID-19 pandemic, puerperal women in a low- and middle-income city had moderate coping difficulties after discharge and were affected by many factors. To meet the different needs of parturients and improve their psychological coping ability, medical staff should perform adequate assessment of social resources relevant to parturients and their families when they are discharged, so they can smoothly adapt to the role of mothers.